(untitled) (Indian Journal of Arid Horticulture, 2025)
Isabgol is a wonder plant with immense laxative utility. It is herb loaded with beneficial soluble fiber. The seed coat known as husk, has medicinal properties and is used as laxative in traditional system of medicine and has been proved beneficial in habitual constipation, chronic diarrhea and dysentery and irritation of digestive tract (Vigar Zaman etal.2002). The progress of any breeding programme depends upon the extent of genetic variability present in the population. The genetic variability along with the heritability gives a reliable picture of the genetic advance to be expected from selection (Burton, 1952) while the heritability coupled with genetic advance aids in predicting the valuable conclusion for effective selection based on phenotypic performance. Correlation studies provide an opportunity to study the magnitude and direction of association of yield with its components and also among various components. To accumulate optimum combination of yield contributing characters in a single genotype, it is essential to know the implication of the interrelationships of various characters along with path coefficients.